If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x) + 4 = 2 x + 4 = 2 Reorder the terms: 4 + x = 2 Solving 4 + x = 2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + x = 2 + -4 Combine like terms: 4 + -4 = 0 0 + x = 2 + -4 x = 2 + -4 Combine like terms: 2 + -4 = -2 x = -2 Simplifying x = -2
| -19=b/14 | | -12.25+4.9w=12.1w-17.7+3.7w | | 2v-5v-8=13 | | x+(x/4)+(x/2)+2=100 | | 18.1=2.1x | | 19x-22+4x=30-3x | | 15+3z=-z-9 | | -3g+18=6g+3 | | 6n+32=-4+6n | | -3q+11-3q=-6q-12 | | g=4q+4z | | 20x=400 | | 7+(-21)= | | =(3k+4)6+7(k+6) | | -6t=-9t+3t | | -10r=180 | | -5y-9+9y=6y+17 | | 9x^2+30x+25x=0 | | 7p-10=-10+7p | | h(t)=-3t^2+36t | | 5e-3=17 | | 7+(x+4)=12 | | 3r+16=16-10r+13r | | 7(s-5)=421 | | 2n+3=3-7n | | 4-8+6b=4+6b | | 5x+104=10x-6 | | =5(9k+2)+8(3+4k) | | 4d-5(3d+10)=126 | | 0=12p+-48 | | -10-4v=-4v | | 0=-3t^2+36t-5 |